Metabolomics of exercise pulmonary hypertension are intermediate between controls and patients with pulmonary arterial hypertension. (October 2019) - Sanders, Jason L.; Han, Yuchi; Urbina, Mariana F.; Systrom, David M.; Waxman, Aaron B.
Mechanisms underlying pulmonary arterial hypertension (PAH) remain elusive. Pulmonary arterial hypertension and exercise PH share similar physiologic consequences; it is debated whether they share biologic mechanisms and if exercise PH represents an early phase of pulmonary arterial hypertension. We conducted an observational study to test if there is a graded metabolic disturbance along the severity of PH, which may indicate shared or disparate pathophysiology. Individuals referred to an academic medical dyspnea center with unexplained exertional intolerance underwent invasive cardiopulmonary exercise testing. We identified controls with no hemodynamic exercise limitation, individuals with exercise PH (mean pulmonary arterial pressure (mPAP) < 25 mmHg at rest but ≥ 30 mmHg during exercise without pulmonary venous hypertension) and pulmonary arterial hypertension (mPAP > 25 mmHg at rest without pulmonary venous hypertension) ( n = 26 in each group). Unbiased metabolomics with chromatography mass spectrometry was performed on pulmonary arterial blood at rest and peak exercise. Random forest analysis and hierarchical clustering were used to quantify metabolite prediction of group membership and rank metabolites which were significantly different between groups. Compared to controls, pulmonary arterial hypertension subjects exhibited perturbations in pathways involving glycolysis, TCA cycle, fatty acid and complex lipid oxidation, collagen deposition and fibrosis, nucleotide metabolism, and others. The metabolic signature of exercise PH was uniquely between that of control and pulmonary arterial hypertension subjects. Accuracy predicting control, exercise PH, and pulmonary arterial hypertension group was 96%, 90%, and 88%, respectively, using paired rest-exercise metabolic changes. Our data suggest the metabolic profile of exercise PH is between that of controls and patients with pulmonary arterial hypertension.